The effectiveness of the educational software based on feedback in developing problem-solving skill in science for third-grade intermediate students in Jeddah - Aljohani, Nouf Hamoud Hamdan (Journal of Educational and Psychological Sciences, 2022)
The aim of this research is to measure the effectiveness of the educational software based on feedback in developing problem-solving skill in science for third-grade intermediate students in Jeddah. The study used the quasi-experimental approach by designing two control and experimental groups, and the achievement test was used as a tool for the study. (60) female students, and the study reached a set of results, the most important of which are: There is a statistically significant difference at the level (0.05) between the mean scores of the experimental group and the control group in the post application of the achievement test in favor of the experimental group. There is no statistically significant difference at the level (0.05) between the mean scores of the experimental group in the post application of the achievement test and the mastery level (90%). ) for problem-solving skills in science in favor of the experimental group, there is a statistically significant difference at the level (0.05) between the mean scores of the control group in the post application of the problem-solving skill test and the level of mastery (90%) for problem-solving skills in science, The effectiveness of an educational software based on feedback to develop problem-solving skill in science for third-grade intermediate students in Jeddah. The study came out with a set of recommendations, the most important of which was the interest in employing educational techniques based on feedback in teaching science because of its role in improving students’ abilities to solve problems in science.